ANALISIS KINERJA KEUANGAN PERUSAHAAN INDUSTRI FARMASI SELAMA MASA PANDEMI COVID-19 - Aulia Refika Zahra Khusuma, (2023)
The purpose of writing this final project is to determine the financial performance during the COVID-19 pandemic in 2020-2021 in state-owned (BUMN) and privately-owned (BUMS) pharmaceutical industry companies with a total of nine companies consisting of two state-owned pharmaceutical industry companies and seven privately-owned pharmaceutical industry companies. When COVID-19 began to spread throughout the world, the impact was felt by everyone, not only people, almost every industrial company also felt the impact caused by COVID-19. Generally, every industrial company is negatively affected by this pandemic, but it does not have a negative impact on the chemical, pharmaceutical and traditional medicine industries. This final project is carried out by collecting secondary quantitative data obtained from the annual reports of pharmaceutical industry companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2021 period. The analysis used is Liquidity Ratio, Profitability Ratio, Solvency Ratio, and Activity Ratio. The results of the analysis found that generally privately owned pharmaceutical industry companies (BUMS) have better financial performance than state-owned pharmaceutical industry companies (BUMN) during the COVID-19. The results of each analysis used in this final project are generally that privately owned pharmaceutical industry companies (BUMS) are superior to state-owned pharmaceutical industry companies (BUMN).